2017
DOI: 10.14715/cmb/2017.63.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen sources on some morphological characteristics of in vitro stevia rebaudiana Bertoni

Abstract: Stevia rebaudiana Bertoni belongs to Asteraceae family that leaves 200-300 times sweeter than sugar. Low seed fertility is one of the most important problems in Stevia production. So, Plant tissue culture is an efficient method for mass propagation of Stevia. In this research, we studied the effect of various concentrations of nitrogen on some morphological traits of stevia under in vitro conditions. We used axillary nodes as explants and they were cultured on Murashige and Skoog (MS) medium containing inorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Akbari et al, (2018) [84] revealed that different doses of nitrogen in growth media influence the growth and expression of UGT85C2, UGT74G1, and UGT76G1 genes in stevia in in vitro conditions. Therefore, evidence from our study and the other recent studies [46,85] suggests that the expression of SGs biosynthetic genes can be manipulated in in vitro conditions. Thus, the development of the commercial production of the high-value rebaudioside A can be achieved through growth media manipulation in tissue cultures in order to meet the increasing demands for natural sweeteners.…”
Section: Discussionsupporting
confidence: 60%
“…Akbari et al, (2018) [84] revealed that different doses of nitrogen in growth media influence the growth and expression of UGT85C2, UGT74G1, and UGT76G1 genes in stevia in in vitro conditions. Therefore, evidence from our study and the other recent studies [46,85] suggests that the expression of SGs biosynthetic genes can be manipulated in in vitro conditions. Thus, the development of the commercial production of the high-value rebaudioside A can be achieved through growth media manipulation in tissue cultures in order to meet the increasing demands for natural sweeteners.…”
Section: Discussionsupporting
confidence: 60%
“…In rapeseeds (Brassica napus) some lncRNAs have been detected to be differentially expressed in cadmium-exposed plants (42). Gene expression has been assayed against different treatments (47)(48)(49)(50). In A. thaliana the expression of 1832 identified lncRNAs were reported to be regulated by various abiotic stresses (51).…”
Section: Discussionmentioning
confidence: 99%
“…High-performance liquid chromatography (HPLC) showed higher stevioside and rebaudioside A content in the leaves of Stevia grown on a PGR-free medium compared with the PGR(s)-containing media. Akbari et al [ 61 ] established a positive effect of the addition of inorganic nitrogen sources, i.e., NH 4 NO 3 (1650 mg/L) and KNO 3 (950 mg/L), to the MS medium on some morphological traits of S. rebaudiana Bertoni derived from axillary nodes as explants. Moreover, the presence of nitrogen sources increases both the shooting and rooting of the plant.…”
Section: Direct Organogenesismentioning
confidence: 99%